MORPHOLOGICAL VARIATION AND ECOLOGICAL ADAPTATION IN PLUMERIA PUDICA - Kavan Shukla; Kunal Odedra; B. A. Jadeja (Jurnal Belantara, 2026)
The present study aimed to conduct a comprehensive integrative morphological and micromorphological assessment of Plumeria pudica Jacq., a widely cultivated ornamental shrub of the family Apocynaceae. Specifically, the research sought to evaluate morphological diversity among seventeen accessions collected from diverse agroclimatic zones of Gujarat and Daman, India, analyze quantitative vegetative and reproductive traits along with qualitative characters, and investigate micromorphological features to understand trait variation, integration, and adaptive significance. Seventeen accessions were systematically examined for quantitative traits including plant height, leaf dimensions, branching pattern, and floral parameters, along with qualitative morphological characteristics. Scanning electron microscopy (SEM) was employed to analyze micromorphological structures of pollen, petal, leaf, stem, and root tissues. Statistical analyses, including Simpson’s and Shannon–Wiener diversity indices, correlation analysis, and hierarchical clustering, were performed to assess intraspecific variation, diversity patterns, and coordinated trait development. Substantial intraspecific variation was observed, particularly in plant height (122–579 cm), leaf size, branching architecture, and floral traits, supported by high diversity index values. SEM analysis revealed distinct pollen exine ornamentation, specialized petal epidermal architecture, variations in stomatal distribution, and root mycorrhizal associations indicative of adaptive strategies. Strong correlations and modular clustering demonstrated coordinated development between vegetative and floral traits. The findings highlight significant phenotypic plasticity and ecological adaptability in Plumeria pudica, providing baseline information for conservation, breeding, and horticultural improvement efforts.